Composition of the plant nuclear envelope theme and variations - Meier, Iris (Journal of experimental botany, 2007)
The nuclear envelope is the hallmark of all eukaryotic cells, separating the nucleoplasm from the cytoplasm. At the same time, the nuclear envelope allows for the controlled exchange of macromolecules between the two compartments through nuclear pores and presents a surface for anchoring and organizing cytoskeletal components and chromatin. Although our molecular understanding of the nuclear envelope in higher plants is only just beginning, fundamental differences from the animal nuclear envelope have already been found. This review provides an updated investigation of these differences with respect to nuclear pore complexes, targeting of Ran signalling to the nuclear envelope, inner nuclear envelope proteins, and the role and fate of the nuclear envelope during mitosis